Marhaban Ya Balapan: A Strategy to Build the Existence of the “Squad Landasan Pacu Ledok” Motorcycle Gang in the Ramadhan Race Phenomenon in Mojokerto - Ulthufna Kausarul Fitriya; Sarmini Sarmini; Nasution Nasution (JSPH (Jurnal Sosiologi Pendidikan Humanis), 2022)
The phenomenon of motorcycle gangs is part of a social culture that is generally formed among young men. Ramadhan Race as an association that manifests expressions and traditions in the month of Ramadan for the Ledok Runway Squad motorcycle gang. The purpose of this study was to describe the tactics of the Ledok Runway Squad motorcycle gang in building an existence in the midst of facing all forms of resistance from society. In addition, this study aims to analyze the dominant factors that influence the Ledog Runway Squad motorcycle gang in building existence at the moment of Ramadhan Race. The method used in this study is qualitative by using a phenomenological approach through observation and in-depth interviews regarding the experiences of motorcycle gang members in building their existence. The results of this study indicate that the strategy for building the existence of motorcycle gangs during the Ramadhan Race moment is: Tricks to convince parents, face the community and avoid policing from the police. The dominant factors for the Ledok Runway Squad moto gang in building its existence are: following global trends, channeling hobbies and entertainment, mechanical betting events and maintaining traditions.